Efficacy and safety of anlotinib combined with 125I seed implantation for iodine-refractory thyroid cancer - Chen, Zhijun; Tang, Xinlan; Tan, Liling; Su, Yu; Wang, Wenjun; Wu, Zhen (Frontiers in Endocrinology, 2025)
Background and objectiveRadioiodine-refractory differentiated thyroid cancer (RAIR-DTC) remains challenging to treat due to a lack of effective therapies. This study aimed to evaluate the efficacy and safety of combining anlotinib with iodine-125 (125I) seed implantation in patients with RAIR-DTC.Methods and materialsWe retrospectively compared three treatment groups in 52 patients with advanced RAIR-DTC: anlotinib monotherapy (Group A, n = 14), 125I seed brachytherapy monotherapy (Group B, n = 25), and combined therapy (Group C, n = 13). Clinical outcomes including local progression-free survival (LPFS), overall survival (OS), tumor response, serum thyroglobulin (Tg) levels, and adverse events were analyzed.ResultsAs of February 2025, the combination therapy group achieved a longer median LPFS (42.2 months) than either monotherapy group (18.6–18.7 months; p = 0.023) and a higher objective response rate at 6 months (77% vs. 21–32% with monotherapies; p < 0.05). Tumor volumes in all groups decreased after treatment, with the greatest reduction within 6 months in the combination group (p < 0.001). By 12 months, response differences between groups narrowed, and median OS was similar across groups (~22–43 months, p = 0.425). Serum Tg levels declined significantly from baseline in all groups. No major procedural complications occurred, and treatment-related adverse reactions were mostly mild (Grade 1–2) and comparable among groups.ConclusionCombining 125I seed brachytherapy with anlotinib demonstrated superior short-term tumor control and prolonged local disease remission in RAIR-DTC, without increasing toxicity. This combination may offer a promising therapeutic option for RAIR-DTC, pending further validation in larger studies.Clinical trial registrationhttps://clinicaltrials.gov, identifier NCT06362772.